2021
DOI: 10.1093/conphys/coab042
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of faecal and caecal microbiota of free-ranging black-tailed prairie dogs (Cynomys ludovicianus) using high-throughput sequencing of the V4 region of the 16S rRNA gene

Abstract: Black-tailed prairie dogs (Cynomys ludovicianus) are keystone species within their grassland ecosystems; their population stability affects a multitude of other species. The goals of this study were to explore, describe and compare the bacterial communities in caecal and hard faecal samples from free-ranging black-tailed prairie dogs (n = 36) from KS, USA, using high-throughput sequencing of the V4 region of the 16S rRNA gene and to compare sex and geographic locations. A total of 22 paired faecal and caecal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…Overall, Bacteroidetes was the most dominant phylum in this study, with Rikenellaceae representing the most dominant group within it. These results are similar to studies on other rodents [85, 86] but not consistent with studies on the fecal and caecal microbiota of black-tailed prairie dogs in Kansas, USA [45] and fecal microbiota of Cynomys ludovicianus in Chihuahua, Mexico [44]. In particular, the proportion of Bacteroidetes accounted for less than 10% of the microbiota in previous studies of black-tailed prairie dogs (Supplementary Information: Table S3), versus 57.3% in this study.…”
Section: Fecal Microbiota Compositionsupporting
confidence: 88%
See 1 more Smart Citation
“…Overall, Bacteroidetes was the most dominant phylum in this study, with Rikenellaceae representing the most dominant group within it. These results are similar to studies on other rodents [85, 86] but not consistent with studies on the fecal and caecal microbiota of black-tailed prairie dogs in Kansas, USA [45] and fecal microbiota of Cynomys ludovicianus in Chihuahua, Mexico [44]. In particular, the proportion of Bacteroidetes accounted for less than 10% of the microbiota in previous studies of black-tailed prairie dogs (Supplementary Information: Table S3), versus 57.3% in this study.…”
Section: Fecal Microbiota Compositionsupporting
confidence: 88%
“…The fecal microbial diversity and abundance have been determined attributed to 10 samples in Janos Biosphere Reserve in Mexico [44]. Recent studies have examined the fecal and cecal microbiota of black-tailed prairie dogs in Kansas focused on 58 samples and compared sex and geographic variation between groups [45]. However, the response of fecal microbiota to habitat and environmental parameters has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, Bacteroidetes was the most dominant phylum in this study, with Rikenellaceae representing the most dominant group within it. These results are similar to studies on other rodents [49,50] but not consistent with studies on the fecal and caecal microbiota of black-tailed prairie dogs in Kansas, USA [45] and fecal microbiota of Cynomys ludovicianus in Chihuahua, Mexico [44]. In particular, the proportion of Bacteroidetes accounted for less than 10% of the microbiota in previous studies of black-tailed prairie dogs (Table S4), versus 57.3% in this study.…”
Section: Fecal Microbiota Compositionsupporting
confidence: 87%
“…Previous work in the fecal microbial diversity and abundance of the species only analyzed a small sample (n = 10) in the Janos Biosphere Reserve in Mexico [44]. Recent study examined the fecal and cecal microbiota of black-tailed prairie dogs in Kansas focused on 58 samples and compared sex and geographic variation between groups [45]. However, the response of fecal microbiota to habitat and environmental parameters has yet to be analyzed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that age, sex, and physiological state are important factors affecting the intestinal ora of dogs [33]. For instance, among captive Beagle and Cocker Spaniel breeds, the abundance of Pseudomonas adaceae and Escherichia is signi cantly higher, while the abundance of Actinobacteria is signi cantly lower in the aged group (> 7 years) than in the adult group (2-7 years) [34].…”
Section: Discussionmentioning
confidence: 98%